Heterogeneously hydrated mantle beneath the late Archean Yilgarn Craton - Ivanic, T.; Nebel, O.; Jourdan, Fred; Faure, K.; Kirkland, Chris; Belousova, E. (2015)
Archean mafic-ultramafic melts, crystallized as layered intrusions in the upper crust and extruded as komatiitic flows, are primary probes of upper mantle chemistry. However, the message from their primary chemical composition can be compromised by different modes of contamination. Contaminants are typically cryptic in terms of their geochemical and isotopic signals but may be related to metasomatised mantle sources, ambient crustal assimilation or subduction-related inputs. In this work we present critical evidence for both dry and wet Archean mantle sources for two juxtaposed layered intrusions in the Australian Yilgarn Craton. The ca. 2813Ma Windimurra and ca. 2800Ma Narndee Igneous Complexes in Western Australia are two adjacent layered intrusions and would be expected to derive via similar mantle sections. A key difference in their chemistry is the presence of crystal-bound water in the Narndee Igneous Complex, represented primarily by abundant hornblende. Such a primary hydrous phase is notably absent in the Windimurra Igneous Complex. New 40Ar/39Ar plateau ages for fresh Narndee hornblende (weighted mean: 2805±14Ma, MSWD=1.8, probability=0.18) agrees with the published U-Pb age of 2800±6Ma for the complex and is consistent with a magmatic origin for this phase. Zircon Hf and whole-rock Hf and Nd isotopes for the Narndee Igneous Complex indicate only minor crustal contamination, in agreement with H and O isotope values in amphibole and O isotope values in rare zircon crystals, plagioclase and pyroxene within both complexes.These findings illustrate a fast temporal transition, in proximal bodies, from anhydrous to hydrous mantle sources with very minor crustal contamination. These large layered mafic-ultramafic intrusions are igneous bodies with a primitive chemical bulk composition that requires large degrees of mantle melting. This has been attributed by many workers to mantle plume activity, yet not without dispute, as subduction-related flux melting may also generate large melt fractions. We conclude that the source of the magmatic water at Narndee is the mantle, which, in conjunction with its absence in the adjacent Windimurra Igneous Complex, argues for a heterogeneous hydration of mantle source regions under the Yilgarn Craton in the Mesoarchean.